Fashion, Society and the First World War International Perspectives - Bass-Krueger, Maude; Edwards-Dujardin, Hayley; Kurkdjian, Sophie (Bloomsbury Academic, 2021)
The historiography of the Great War has been significantly renewed in recent years, yet, despite its crucial social, economic, and cultural importance, the role that fashion played in shaping wartime experiences and economies has not yet been addressed. This collection fills this gap in the literature by examining the impact the Great War had on fashion, its industry, and civilians in a transnational context. With contributions from leading experts, Fashion, Society and the First World War explores wartime style and the reframing of selfhood, gender roles, and national identity through clothing and print culture.